The Effect of Room Temperature on the Spread of the Covid-19 Virus by Creating a Special Isolation Room with a Hot Temperature for Those Indicated as Medical Service Facilities - Anwar, Hendi (Indonesian Journal of Visual Culture, Design, and Cinema, 2022)
During the Covid-19 pandemic, there were many alternatives to anticipate or anticipate through certain tools and media with less effectiveness and endanger the users, for example, a device that can be called a disinfecting chamber or "disinfection chamber". Quoted from CNN Indonesia, sourced from the WHO Indonesia Twitter account that not to spray alcohol or chlorine directly on the body, spraying such chemicals can be dangerous if exposed to clothing or mucous membranes (example: eyes, mouth) . Alcohol and chlorine can be used on the surface of the body with instructions or user guides. With an official statement from the world health organization directly that it can endanger health, there must be a breakthrough in new media that is safer for users . According to scientists from Aix-Marseille University in France, if the corona virus is exposed to high temperatures it can reduce the life span of the virus itself or can kill the virus itself at 92 degrees Celsius within 15 minutes (quoted from DetikHealt.com) . Giving heat to the room itself using heating by providing steam as in the sauna room and the interior elements are also applied special heat-resistant materials without compromising the safety and health of the users of the room . Then this room will be in health centers that move to handle patients who are examined and also useful for medical practitioners who treat patients . With a room that has a high temperature is expected to minimize the spread of the virus on an ongoing basis and neutralized our bodies outside of the virus in a safe way , because reported by various news , the specialists in internal medicine provide a statement that the virus that is outside the host or can be called a part of our body can last within 3 hours without handling such as washing hands using a handsanitizer or other treatments . The output of the research itself is a room with a hot temperature with wood material and the shape of the room adapts to the needs and existing literature, Then the benefits of this research can be realized a tool to inhibit the spread of the Covid-19 virus and can be used as much as possible for health workers and people who need it. Key Word : Covid-19, Disinfection Chamber , Isolation Room